CIRCULATION OF ARBOVIRUSES AND INFLUENZA VIRUS IN PRIBAIKALYE - E. A. Tchaporgina; G. A. Danchinova; M. A. Khasnatinov; A. V. Liapunov; S. V. Pyzhjanov; E. V. Arbatskaya (Acta Biomedica Scientifica, 2012)
The California encephalitis serogroup virus, Batai virus and Geta virus were isolated as result of investigation of distribution of arboviruses in Pribaikalye. The results of the study of influenza A virus in birds in Pribaikalye are presented as well.